Join the Fiesta in Support of the United Farm Workers, AFL-CIO with Gov. Jerry Brown and Cesar Chavez
Flyer advertising an event in support of the United Farms Workers (UFW) with Governor Jerry Brown and Cesar Chavez. N.d. Circa 1975.